Early rhythm control vs. rate control in atrial fibrillation: A systematic review and meta-analysis - Han, Shaojie; Jia, Ruikun; Cen, Zhifu; Guo, Ran; Zhao, Shenyu; Bai, Yixuan; Xie, Min; Cui, Kaijun (Frontiers in Cardiovascular Medicine, 2023)
Objective It has long been debated whether rhythm control vs. rate control strategies have differing effects on mortality and morbidity for atrial fibrillation (AF). Recently, several randomized controlled studies (RCTs) and observational trials described that an early rhythm management method was linked to a lower likelihood of negative clinical outcomes in individuals with AF. We wanted to see if an early rhythm management method may help patients with AF. Methods We performed a systematic search to retrieve studies assessing the outcomes of early rhythm control vs. rate control in AF by using PubMed, Web of Science, Cochrane Library, and Embase published between 01/01/2000 and 15/04/2022. Results Finally, two RCTs, one retrospective analysis of RCTs, and four observational studies were identified. Compared with rate control, early rhythm control has been linked to lower all-cause mortality. [risk ratio (RR), 0.76; 95% CI 0.69–0.83; P < 0.00001; I2 = 77%]. The early rhythm control group was also associated with a lower risk of cardiovascular mortality (RR, 0.68; 95% CI 0.63–0.74; P < 0.00001; I2 = 33), stroke (RR, 0.77; 95% CI 0.67–0.87; P < 0.001; I2 = 64), and heart failure hospitalization (RR, 0.74; 95% CI 0.59–0.93; P = 0.0009; I2 = 93%). We found no significant difference in nights spent in hospital per year, acute coronary syndrome, major bleeding, and cardiac arrest/ventricular arrhythmia between the groups. Conclusion In this meta-analysis, early rhythm therapy was linked to a lower risk of all-cause mortality, cardiovascular mortality, stroke, and heart failure hospitalization compared with the rate control group. Systematic review registration https://www.crd.york.ac.uk/PROSPERO/, identifier CRD42022333592.